PERAN PANITERA PENGGANTI DALAM MENGOPTIMALKAN JALANNYA PERSIDANGAN DI PENGADILAN AGAMA SORONG - Kitaby Ansar, Magfirah Ummul; Umrah, St. (Prodi Hukum Keluarga (Akhwal Syahsiyyah) IAIN Sorong, 2024)
This research aims to analyze the role of substitute clerks in optimizing the course of trials at the Sorong Religious Court. The method used in this research is qualitative. The results of his research show that substitute clerks have a very important role in ensuring the efficiency and effectiveness of trials. The tasks carried out during the trial process greatly contribute to the smooth running of the trial process. This research concludes that optimizing the performance of substitute clerks can be one of the keys to improving the quality of judicial services at the Sorong Religious Court.